2010
DOI: 10.1258/la.2010.009049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of haematology, coagulation and clinical chemistry parameters in blood samples from the sublingual vein and vena cava in Sprague–Dawley rats

Abstract: The investigation of clinical pathology parameters (haematology, clinical chemistry and coagulation) is an important part of the preclinical evaluation of drug safety. However, the blood sampling method employed should avoid or minimize stress and injury in laboratory animals. In the present study, we compared the clinical pathology results from blood samples collected terminally from the vena cava (VC) immediately before necropsy with samples taken from the sublingual vein (VS) also prior to necropsy in order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…There was a corresponding decrease in lymphocyte count. This is in consonance with Provencher et al [33] who stated that in mice, lymphocyte counts decrease as neutrophil counts increase. The observed increase in neutrophil count indicates that neutrophils probably functioned as APCs, leading to increased activation of antigen-specific B lymphocytes as observed from the data on humoral immune responses.…”
Section: Plos Onesupporting
confidence: 89%
“…There was a corresponding decrease in lymphocyte count. This is in consonance with Provencher et al [33] who stated that in mice, lymphocyte counts decrease as neutrophil counts increase. The observed increase in neutrophil count indicates that neutrophils probably functioned as APCs, leading to increased activation of antigen-specific B lymphocytes as observed from the data on humoral immune responses.…”
Section: Plos Onesupporting
confidence: 89%
“…Additionally, this study included data from blood collected from the cranial vena cava and jugular vein, as well as directly from the heart. In rodents, hematologic and biochemical parameters can vary when blood is collected from different anatomical locations [22][23][24][25][26][27]. It should also be noted that all guinea pigs in this study were housed in Colorado at an elevation of approximately 5,000 ft, which may impact certain RBC parameters.…”
Section: Plos Onementioning
confidence: 99%
“…It has also been reported that the site of sample (blood) collection plays a vital role in the resulting parameters. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%